Tra norma e uso: la dislocazione a sinistra nelle grammatiche di italiano per apprendenti stranieri - Buttini, Valeria (My University, 2015)
In this paper, I will observe how 34 recent Italian grammars for foreigners describe and illustrate the left-dislocation. Three different types of grammars sharing similar attitudes towards the construction have been found: (1) shy grammars, in which the left-dislocation is sometimes briefly described from a formal point of view, but very often found in the sentences given as examples of Italian language when describing other linguistic phenomena; (2) oblivious grammars, in which the left-dislocation is neither described nor included in the sentences given as examples of Italian language; (3) aware grammars, in which the left-dislocation is described in detail from both a formal and functional point of view and where a more or less rich presence of the construction is found in the exemplifications. A deeper analysis will highlight other features each type of grammar shares, such as the educational/professional background of the authors and the intended audience of the grammar being students of Italian as a second language or as a foreign language. These features are factors that play a role in the treatment received by the left-dislocation.
Keywords: left dislocation; grammar textbooks; Italian as a second language